COVID-19: Assessing the impact of lockdown on recreational athletes - Martin, A. M.; Champ, F.; Franklin, Z. (Psychology of Sport and Exercise, 2021)
Background and Aims: The COVID-19 pandemic has resulted in associated lockdown restrictions for individuals across England, including the postponement of all recreational sporting provisions. The beneficial effects of regular physical activity are well established yet to the authors' knowledge, no research addresses the cancellation of all recreational provisions. Using quantitative and qualitative methods, this study assessed the impact of COVID-19 restrictions on recreational sports players, what alternative exercise methods have been sought and how players feel about returning to their sport. Method: An online survey was distributed across England for six-weeks commencing in May 2020. A questionnaire explored differences in the impact of COVID-19 restrictions between sex, winter/summer/year-round sports, team/individual sports, age, and resilience groups. The use of alternative exercise methods, coping strategies and feelings about returning to sport were also investigated. Responses were gathered from 2023 adults whose recreational sport had been cancelled by COVID-19. All completed questionnaires (n= 1213) were taken for analysis (mean age = 49.41 years, SD = 17.165, 55.2% female). Results: Quantitative findings showed the negative impact of COVID-19 restrictions was greater for females, those involved in winter and team sports, those aged 18-39 and low-resilient copers (p<0.05). No significant differences were found between individuals that had had COVID-19 or were considered vulnerable by government guidelines. Acceptance was the most common coping strategy. The average number of days per week that participants exercised significantly increased during lockdown, with significant increases also seen in the use of online workouts, fitness apps and home-gym exercise. Qualitative findings suggested that participants are looking forward to the social and physical benefits of recreational activity restarting yet are concerned about the logistics of returning under social distancing restrictions. Other worries included loss of fitness, spreading (younger age groups) and catching (older age groups) COVID-19 and being in a crowd. Conclusions: Results highlight what is currently accessible to home-based exercisers and inform the reintroduction of recreational sports clubs. As COVID-19 restrictions look to persist, club representatives should provide accessible home-exercise options and be cautious of participant concerns when considering the return of recreational sport.